Studying Abroad as a Means of Preparing Future Music Teachers in China - Ziwen Wang (Educational Challenges)
The concept of studying abroad as a means of preparing future music teachers in China has a rich and complex history, reflecting the nation’s evolving educational philosophies, political changes, and cultural exchanges.